TRANSMISI KEBIJAKAN MONETER BANK INDONESIA KE PASAR UANG PADA MASA KETIDAKPASTIAN EKONOMI GLOBAL PERIODE NOVEMBER 2008 â NOVEMBER 2012 - , PASITHESA PUTRI J ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study intends to know the relationships between official rate (BI Rate) to various overnight rates in interbank money market (overnight interbank call money rate in the morning, overnight interbank call money rate in the afternoon, and overnight JIBOR). Using monthly data since November 2008 until November 2012, examining the relationship helped to ensure the success of monetary policy transmission in money market, necessarily in uncertain global economic condition. This study used various analytical tools, started from Johansen cointegration test, VAR/ VECM, impulse response function, to forecast error variance decomposition. This study found long and short run relationships between BI Rate and various overnight rates in interbank money market. Thus, the first step of monetary policy transmission in money market has been done successfully, although uncertain global economic condition existed. Furthermore, shocks in BI Rate immediately responded by overnight rates, and those responses were positive. From forecast error variance decomposition analysis, the writer concluded that in the short run, BI Rate variation was influenced by its own effect. On the other hand, in the long run, the contributions of overnight rates were getting bigger. The contribution of BI Rate in explaining overnight rates variability remained exists, although the percentages were small.